Characteristics of Risk Factors for Chronic Suppurative Otitis Media at Ibnu Sina Hospital, Makassar City in 2022-2023 - Abas, Wahyu Julianto; Sam, Andi Dhedhie Prasatia; Arifuddin, Andi Tenri Sanna; Abidin, Moh. Reza Zainal; Masdipa, Andi (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Chronic Suppurative Otitis Media (CSOM) is a persistent middle ear infection that significantly contributes to global hearing loss and reduced quality of life, yet recent epidemiological data from major Indonesian cities such as Makassar remain scarce. Objective: To identify risk factor characteristics, including age, gender, and CSOM type (benign or malignant), among patients diagnosed at Ibnu Sina Hospital, Makassar, from 2022 to 2023. Methods: A quantitative descriptive study with a retrospective design was conducted using total sampling of 31 patient medical records meeting inclusion criteria, and data were analyzed univariately to present frequency distributions and percentages. Results: The 17–25-year age group had the highest CSOM prevalence (35.48%), followed by the 0–5-year group (16.13%). Female patients accounted for 51.61%, showing a nearly equal gender distribution. The majority of cases were benign CSOM (96.77%), with only 3.23% classified as malignant. These findings indicate that young adults represent the most affected demographic, likely due to environmental exposure and untreated upper respiratory infections, while malignant CSOM remains rare. Conclusion: Age is the primary risk factor for CSOM in this population, with young adults being the most vulnerable, underscoring the importance of targeted preventive measures and early ear health education.